Superovulation Using the Combined Administration of Inhibin Antiserum and Equine Chorionic Gonadotropin Increases the Number of Ovulated Oocytes in C57BL/6 Female Mice - Takeo, Toru; Nakagata, Naomi (PLOS ONE, 2015)
Superovulation is a reproductive technique generally used to produce genetically engineered mice. Superovulation in mice involves the administration of equine chorionic gonadotropin (eCG) to promote follicle growth and then that of human chorionic gonadotropin (hCG) to induce ovulation. Previously, some published studies reported that inhibin antiserum (IAS) increased the number of ovulated oocytes in ddY and wild-derived strains of mice. However, the effect of IAS on the C57BL/6 strain, which is the most widely used inbred strain for the production of genetically engineered mice, has not been investigated. In addition, the combined effect of IAS and eCG (IASe) on the number of ovulated oocytes in superovulation treatment has not been examined. In this study, we examined the effect of IAS and eCG on the number of ovulated oocytes in immature female mice of the C57BL/6 strain in superovulation treatment. Furthermore, we evaluated the quality of obtained oocytes produced by superovulation using IASe by in vitro fertilization (IVF) with sperm from C57BL/6 or genetically engineered mice. The developmental ability of fresh or cryopreserved embryos was examined by embryo transfer. The administration of IAS or eCG had a similar effect on the number of ovulated oocytes in C57BL/6 female mice. The number of ovulated oocytes increased to about 3-fold by the administration of IASe than by the administration of IAS or eCG alone. Oocytes derived from superovulation using IASe normally developed into 2-cell embryos by IVF using sperm from C57BL/6 mice. Fresh or cryopreserved 2-cell embryos produced by IVF between oocytes of C57BL/6 mice and sperm from genetically engineered mice normally developed into live pups following embryo transfer. In summary, a novel technique of superovulation using IASe is extremely useful for producing a great number of oocytes and offspring from genetically engineered mice.